Study of Student Satisfaction in Using the Moodle E-Learning System: PLS-SEM Approach - April Lansonia; Matthias Austin; Eiser Aaron Beldiq (CORISINTA, 2024)
This research investigates the factors influencing student satisfaction in using the Moodle E-Learning system in a higher education environment. We apply the Structural Equation Modeling Partial Least Squares (SEM PLS) method to ex- plore the relationship between relevant variables, such as Moodle system quality, service quality, learning quality, level of system use, and student perceptions of their satisfaction. This research uses data collected from a sample of students who use Moodle as an E-Learning platform. The results of the SEM PLS analy- sis will provide insight into the influence of each variable on student satisfaction and how these factors are interconnected. The results of this research will help higher education institutions increase the use of Moodle as an effective online learning tool. In addition, the findings of this research will provide a deeper understanding of the critical elements that influence student satisfaction in the E-Learning context.